Strengthening RC square columns with UHP-ECC section curvilinearization and FRP confinement: Concept and axial compression tests. (1st April 2023) - Zeng, Jun-Jie; Liang, Qi-Jin; Cai, Wei-Jian; Liao, JinJing; Zhou, Jie-Kai; Zhu, Jiong-Yi; Zhang, Lihai
Highlights: A novel strengthening technique incorporating section curvilinearization (SC) using UHP-ECC and FRP confinement is proposed. Large-scaled FRP-confined square RC columns with SC using UHP-ECC were prepared and tested. Parameters of FRP thickness, the rise-to-span ratio and the strength of the additive concrete were investigated. The current design models for FRP-confined curvilinearized RC columns were assessed by the experimental results. Abstract: In this paper, a novel column strengthening technique incorporating section curvilinearization (SC) using ultra-high performance engineered cementitious composites (UHP-ECC) and fiber-reinforced polymer (FRP) confinement is proposed and validated. Eleven large-scaled FRP-confined square reinforced concrete (RC) columns with SC using UHP-ECC as the additive material were prepared and tested. The main parameters investigated in this paper included the FRP thickness, the rise-to-span ratio, and the strength of the additive concrete. Test results show that the SC technique with FRP jacketing and UHP-ECC as the additive material enhances the load-bearing capacity of the RC columns by 52% with a 17% section increment. By assessing the existing design-oriented stress–strain models of confined concrete in curvilinearized square columns (CSCs) using the test results obtained in this study, it reveals that the current models could underestimate the ultimate strength of the confined concrete in CSCs with a two-layer FRP wrap, and therefore further research on the improvement on the stress–strain model of confined concrete in CSCs becomes necessary.